2001
DOI: 10.13031/2013.2296
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Site-Specific Management Zones by Unsupervised Classification of Topographic Attributes and Soil Electrical Conductivity

Abstract: The objective of this research was to determine if unsupervised classification of topographic attributes and soil electrical conductivity could identify management zones for use in precision agriculture. Data collected in two fields located in central Missouri were used to test the proposed methodology. Principal component analysis was used to determine which layers of data were most important for representing within-field variability. Unsupervised clustering algorithms implemented in geographic information sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
147
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(164 citation statements)
references
References 11 publications
3
147
1
13
Order By: Relevance
“…Several studies have indicated that homogenous management zones could be used as an alternative to grid soil sampling and to develop nutrient maps for variable rate fertilizer application (Khosla and Alley, 1999;Fleming et al, 2000a). Spatially coherent areas within fields may also be useful in relating yield to soil and topographic parameters for crop-modeling evaluation (Fraisse et al, 2001a While methods for delineating management zones vary widely in the information used, usually they are based on soil and yield information possibly over several years (Fraisse et al, 2001b;Fleming et al, 2000b). Many researches used the soil and/or relief information to define management zones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that homogenous management zones could be used as an alternative to grid soil sampling and to develop nutrient maps for variable rate fertilizer application (Khosla and Alley, 1999;Fleming et al, 2000a). Spatially coherent areas within fields may also be useful in relating yield to soil and topographic parameters for crop-modeling evaluation (Fraisse et al, 2001a While methods for delineating management zones vary widely in the information used, usually they are based on soil and yield information possibly over several years (Fraisse et al, 2001b;Fleming et al, 2000b). Many researches used the soil and/or relief information to define management zones.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches used the soil and/or relief information to define management zones. For example, Fraisse et al(2001b) used a combination of topographic attributes and soil electrical conductivity (EC) to delineate management zones. Schepers et al (2004) aggregated the landscape attributes into management zones to characterize spatial variability in soil chemical properties and corn yields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation attribute was selected to define the MZs for the three areas based on the results found by several authors, such as Bazzi et al (2015), Fraisse et al 2001, Jaynes et al (2005, Peralta and Costa (2013), Schenatto et al (2016), and Schepers et al (2004), which suggest that when the area is not flat, the variable elevation frequently has a spatial association with crop yield. …”
Section: Resultsmentioning
confidence: 99%
“…In the process of generating MZs, clustering methods have been widely used (FRAISSE et al, 2001;LI et al, 2007;REYNIERS et al, 2006;SCHENATTO et al, 2016;TAYLOR et al, 2003). The algorithm Fuzzy C-Means (BAZZI et al, 2013;LI et al, 2007;MORARI et al, 2009;MILNE et al, 2012;XIN-ZHONG et al, 2009) is a clustering method based on the fuzzy logic, defined by Zadeh (1965), which matches uncertainties associated with class and association boundaries (DOBERMANN et al, 2003).…”
Section: Introductionmentioning
confidence: 99%